AIDA Analysis of Creative Instagram Ads: A Case Study of @universalmusicindonesia - Pringgodarmo, Auryn Amorivia (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research analyzes the AIDA model (Attention, Interest, Desire, Action) that Universal Music Indonesia uses to promote its artists. The AIDA model becomes an effective model in developing the marketing strategies of the company. A qualitative method was employed and data was collected using ten unstructured interviews with respondents who had come across Universal Music Indonesia’s ads on Instagram (@universalmusicindonesia). It was found that the AIDA model is an important factor for the development of the Universal Music Indonesia’s marketing strategies and for a successful promotion of its services. The creative advertisements posted by Universal Music Indonesia are the main reason for this interaction. The AIDA model is of great value in as far as marketing effectiveness of creative advertisement is concerned. Music labels should not ignore some elements of the AIDA model when developing their creative ad campaigns. This study is not without limitations, including the small number of respondents and the focus on only one platform, Instagram. Future studies are encouraged to cover perspectives from the business side and broaden the analysis to more social networks.